The effect of organically derived fertilisers on early growth of Pinot noir cuttings under glasshouse conditions. Issue 3 (3rd July 2017) - Hodge, S.; Merfield, C. N.; Creasy, G. L.
ABSTRACT: This study examined the effects of organically-derived plant growth promoters (PGPs) on vegetative growth of Pinot noir cuttings under glasshouse conditions for 8 weeks. Solutions of 10 products were applied four times, 2 weeks apart, as a soil drench. In standard potting mix, none of the products caused significant increases in vegetative growth. In low-nutrient potting mix, three products (Synerlogic, Actavize, Just Fish) increased aspects of growth, such as leaf number, shoot length and shoot and root dry weight. These products were relatively high in NPK, and therefore cutting growth was positively correlated to concentrations of NPK in the added solutions. The results imply that addition of PGPs does not by default enhance growth of grape cuttings, and that the mechanism of growth enhancement appears to be simple nutrient provision, rather than by a more complex physiological route involving plant hormones or hormone mimics.